RESOURCE UTILIZATION LEVEL’S ANALYSIS OF YELLOWFIN TUNA (Thunnus albacares) FISHERIES IN THE MENTAWAI WATERS OF WEST SUMATRA - Muhammad Dede S.; Abdullah Munzir; Junaidi Junaidi (Universitas Mataram, 2026)
The high economic dependence of fishing communities on yellowfin tuna makes them vulnerable to fluctuations in catch and market prices. This study aims to analyze the level of fishery resource utilization, which is crucial for ensuring the sustainability of yellowfin tuna fisheries in Mentawai waters. This study used a quantitative descriptive approach to analyze the level of utilization of yellowfin tuna (Thunnus albacares) fishery resources in Mentawai waters landed at the Bungus Ocean Fisheries Port (PPS), West Sumatra. The CPUE (Customer Equity Index) of yellowfin tuna in the Indonesian Fisheries Authority (WPPNRI) 572 decreased from 2019 to 2024, indicating a decline in stock abundance and increasing fishing pressure, while the utilization rate shifted from underfishing to overfishing (2019–2024). MSY analysis using the Schaefer and Fox model indicates a sustainable utilization limit of 400–487 trips per year, but actual efforts have exceeded this limit, necessitating data-driven adaptive management to maintain stock sustainability. It is recommended to limit the number of trips, establish a minimum catch size, and conduct regular monitoring of CPUE and length distribution to support science-based policymaking.